Nitrogen Addition Changes the Stoichiometry and Growth Rate of Different Organs in Pinus tabuliformis Seedlings - Jing, Hang; Zhou, Haoxiang; Wang, Guoliang; Xue, Sha; Liu, Guobin; Duan, Mengcheng (Frontiers in Plant Science, 2017)
Background. Nitrogen (N) deposition could influence plant stoichiometry and growth rate and thus alter the structure and function of the ecosystem. However, the mechanism by which N deposition changes the stoichiometry and relative growth rate (RGR) of plant organs, especially roots with different diameters, is unclear. Methods. We created a gradient of N availability (0–22.4 g N m–2 year–1) for Pinus tabuliformis seedlings for 3 years and examined changes in the carbon (C):N:phosphorus (P) ratios and RGRs of the leaves, stems, and roots with four diameter classes (finest roots, <0.5 mm; finer roots, 0.5–1 mm; middle roots, 1–2 mm; and coarse roots, >2 mm). Results. (1) N addition significantly increased the C and N contents of the leaves and whole roots, the C content of the stems, the N:P ratios of the leaves and stems, and the C:P ratio of the whole roots. (2) In the root system, the C:N ratio of the finest roots and the C:P ratios of the finest and finer roots significantly changed with N addition. The N:P ratios of the finest, finer, and middle roots significantly increased with increasing amount of N added. The stoichiometric responses of the roots were more sensitive to N addition than those of the other organs (3) The RGR of all the organs significantly increased at low N addition levels (2.8–11.2 g N m–2 year–1) but decreased at high N addition levels (22.4 g N m–2 year–1). (4) The RGRs of the whole seedlings and leaves were not significantly correlated with their N:P ratios at low and high N addition levels. By contrast, the RGRs of the stems and roots showed a significantly positive correlation with their own N:P ratio only at low N addition level. Conclusions. Addition of N affected plant growth by altering the contents of C and N; the ratios of C, N, and P; and the RGRs of the organs. RGR is correlated with the N:P ratios of the stems and roots at low N addition level but not at high N addition level. This finding is inconsistent with the growth rate hypothesis.